Inkubasi Kewirausahaan Berbasis Mahasiswa untuk Pengembangan Usaha Digital Startup Mahasiswa untuk mengoptimalkan Usaha Mahasiswa yang Berkelanjutan - Harumy, THF.; Br.Ginting, Dewi Sartika; Manik, F.Y.; Nuzuliati, Nuzuliati (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
The digital startup business incubation program for students is an initiative to support the development of innovative and sustainable businesses. The program aims to help students develop competitive business potential. The entrepreneurial landscape at Universitas Sumatera Utara is continuously growing, marked by the emergence of young entrepreneurs from various programs such as the Student Entrepreneurial Program (PMW) and the Student Creativity Program (PKM). In 2023, there were 12 funding opportunities for PKM entrepreneurial schemes and three winners of the P2MW program. However, challenges remain, such as limited networking opportunities, market access, and minimal mentoring and education on financial management. The lack of mentors and supporting resources often causes campus startups to lose motivation. The methods used to address these issues include mentoring to enhance the capabilities of student startups, financial management literacy, the provision of business facilities, and training and guidance in marketing. This program provides valuable opportunities for students to develop digital business ideas and apply sustainable business principles. As a result, students are better prepared to contribute to sustainable economic growth.Keywords: startup; incubator; digital; sustainable; business Abstrak:  Program inkubasi pengembangan usaha startup digital mahasiswa merupakan inisiatif untuk mendukung pengembangan usaha yang inovatif dan berkelanjutan. Tujuan program ini adalah membantu mahasiswa mengembangkan potensi usaha yang kompetitif. Situasi kewirausahaan di Universitas Sumatera Utara terus berkembang dengan munculnya wirausahawan muda dari berbagai program, seperti Program Wirausaha Muda (PMW) dan Program Kreativitas Mahasiswa (PKM). Pada tahun 2023, terdapat 12 pendanaan untuk skema kewirausahaan PKM dan tiga pemenang program P2MW. Namun, masih terdapat kendala berupa keterbatasan peluang jejaring, akses pasar, serta minimnya pendampingan dan edukasi terkait pengelolaan keuangan usaha. Kurangnya mentor dan sumber daya pendukung menyebabkan startup kampus sering kehilangan motivasi. Metode yang digunakan untuk mengatasi permasalahan ini meliputi pendampingan peningkatan kemampuan startup mahasiswa, literasi pengelolaan keuangan, penyediaan fasilitas usaha, serta pelatihan dan bimbingan pemasaran. Program ini membuka peluang berharga bagi mahasiswa untuk mengembangkan ide bisnis digital dan menerapkan prinsip bisnis berkelanjutan. Hasilnya, mahasiswa lebih siap berkontribusi pada pertumbuhan ekonomi yang berkelanjutan.Kata kunci: startup; inkubator; digital; berkelanjutan; bisnis